Antioxidant and Hepatoprotective Effects of Chitosan on High Fructose Induced Liver Damage in Albino Rats - AL-Kurdy, Masar J.; Kazaal, Meraim A. (Iraqi Journal of Science, 2024)
Chitosan is a biodegradable natural polymer with many advantages such as nontoxicity, biocompatibility, and biodegradability. The current study aimed to evaluate the role of chitosan in reducing or regulating liver disorders caused by high fructose.concentration. The study was performed on thirty-two Wistar male rats, weighing between 195-200gms. These rats divided into four groups: control group which was kept on distill water, group 2 (G2) dosed with 40% fructose, group 3 (G3) dosed with 250 mg/kg of chitosan and group 4 (G4) dosed with 40% fructose and 250 mg/kg chitosan. After four weeks of study the blood samples were taken by heart puncturing and then all animals were sacrificed and specimens from liver were taken and homogenized for Alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase activity (ALP), and superoxide dismutase (SOD) determination. Liver tissues blocks were prepared by paraffin method stained using hematoxylin and eosin (H&E) stain. Highest concentration of ALT, AST, ALP, and SOD was detected in group G2 while serum albumin level decreased in rats in that group. We also found clear histological disorders in the liver of rats of this group. A reduction in the liver damage in G4, as the role of chitosan (G3) in improving liver function was proven by converging the level of the studied indicators from its counterpart in the control group. It can be concluded that chitosan is a successful protective agent for liver function: as it reduced hepatic impairment resulting from the use of fructose.